153k views
5 votes
PLEASE HELP 100 POINTS!!!

Complete the proof.

If 6+5x+3=−4x , then x=−1 .

Drag and drop the reasons to correctly complete each box.

PLEASE HELP 100 POINTS!!! Complete the proof. If 6+5x+3=−4x , then x=−1 . Drag and-example-1
User Aviran
by
6.1k points

2 Answers

0 votes

here is your answer.

4x − 1 = −2 (x + 1) ⇒ Given

have a good day.

User Cbowns
by
5.5k points
2 votes

Answer: AND Step-by-step explanation:

4x − 1 = −2 (x + 1) ⇒ Given

4x−1=−2x−2⇒ Distributive property (since we've multiplied out -2(x+1))

6x−1=−2 ⇒ Addition or Subtraction Property of Equality (We've added 2x onto the 4x to get 6x)

6x=−1 ⇒ Commutative Property (We've moved -1 to the other side to get the sum -2+1 = -1)

x=−¹/₆ ⇒ Multiplication or Division Property of Equality (We divided both sides by 6)

User Elevener
by
5.1k points